THE IMPACT OF OMNICHANNEL STRATEGY ON CUSTOMER EXPERIENCE IN THE DIGITAL ERA - Prabowo Tejo Susetyo; Siti Dyah Handayani; Retno Widowati (Asosiasi Dosen Muda Indonesia, 2024)
Omnichannel is the latest form of marketing strategy from the terms multichannel and crosschannel. Omnichannel can be explained that business actors carry out marketing from digital channels and also offline. Everything is done in one hand effectively and efficiently. This research method is carried out with a qualitative approach and the Systematic Literature Review (SLR) method. This data source uses secondary data sources, namely from journal articles that have a national and international reputation. Articles that meet the criteria were obtained as many as 12 articles. The results of the study are based on research results with the topic of omnichannel strategy influencing customer experience, most of which state that it has had an influence. Customer experience in making transactions for goods or services can be done online first or can also visit the store offline. Customer experience activities can be carried out efficiently and more effectively because the desired brand or product information has been obtained previously.